Group decision making with unbalanced-expertise - Sorooshian, Shahryar (Institute of Physics Publishing, 2018)
Problem complexities have forced the decision makings techniques to shift to a more dynamic approach. In this study, a mixed decision-making methodology is introduced which integrates multi-attribute decision-making (MADM) techniques with qualitative group decision making approaches (Delphi, Brainstorming, and Nominal group technique). In addition, this study proposes a generalizable new multi-attribute group decision-making approach, with a group of experts who have a non-equal level of expertise. Feasibility of the proposed approach is tested with a case of a factor rating (Weighted Score method) MADM.